Tris‐Functionalized Hybrid Anderson Polyoxometalates: Synthesis, Characterization, Hydrolytic Stability and Inversion of Protein Surface Charge. Issue 12 (10th February 2015) - Blazevic, Amir; Al‐Sayed, Emir; Roller, Alexander; Giester, Gerald; Rompel, Annette
Abstract Single‐ and double‐sided functionalized hybrid organic–inorganic Anderson polyoxomolybdates with GaIII and FeIII positioned as central heteroatoms have been synthesized in a mild, two‐step synthesis in an aqueous medium. Compounds 1–4 were isolated as hydrated salts, [TBA]3[GaMo6O18(OH)3{(OCH2)3CCH2OH}]×12 H2O (1) (TBA=tetrabutylammonium), Na3[FeMo6O18{(OCH2)3CCH2OH}2]×11 H2O (2), [TMA]2[GaMo6O18(OH)3{(OCH2)3CNH3}]×7 H2O (3) (TMA=tetramethylammonium), and Na[TMA]2[FeMo6O18(OH)3{(OCH2)3CNH3}](OH)×6 H2O (4). All the compounds were characterized based on single‐crystal X‐ray diffraction (SXRD), FTIR, UV/Vis, thermogravimetric, ESI‐MS, NMR, and elemental analyses. Compound 1 was also crystallized with two smaller organic cations, giving [TMA]3[GaMo6O18(OH)3{(OCH2)3CCH2OH}]×n H2O (5) and [GDM]3[GaMo6O18(OH)3{(OCH2)3CCH2OH}]×n H2O (6) (GDM=guanidinium) and were characterized based on UV/Vis, NMR, FTIR, and elemental analyses. The use of these compounds as additives in macromolecular crystallography was investigated by examining their hydrolytic stability by using ESI‐MS in a pH range of 4 to 9. Sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) analysis showed that BSA remains intact in a solution containing up to 100 equivalents of 1 or 4 over more than four days at 20 °C. Zeta potential measurements demonstrate that 1–4 induce charge inversions on the positively charged surface of BSA (1 mg mL−1) with concentrations starting as low as 1.29 mM for compounds 1 and 2, which have the highest negative surface charge.